1994
DOI: 10.1007/bf02767726
|View full text |Cite
|
Sign up to set email alerts
|

Renal clearance of endogenous erythropoietin in patients with proteinuria

Abstract: Recent data indicated the importance of urinary losses of erythropoietin (Epo) in the pathogenesis of anaemia in patients with nephrotic syndrome. In the present study we aimed to investigate plasma and urinary Epo levels and their renal handling in relation to beta 2-microglobulin (beta 2m), sodium metabolism and the renin-angiotensin-aldosterone system (RAAS), respectively, in patients with sub-nephrotic range proteinuria (SNP), microalbuminuric diabetics and hypertensives, and in healthy subjects studied on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…In chronic renal insufficiency, a decreased Epo production leads to anemia, usually with creatinine clearance lower than 40 mL/min/1.73 m 2 [8]. Therefore, the presence of CRI in FAP patients is a relevant parameter to explain, at least in part, the finding of inappropriately low Epo values in anemic patients.…”
Section: Discussionmentioning
confidence: 95%
“…In chronic renal insufficiency, a decreased Epo production leads to anemia, usually with creatinine clearance lower than 40 mL/min/1.73 m 2 [8]. Therefore, the presence of CRI in FAP patients is a relevant parameter to explain, at least in part, the finding of inappropriately low Epo values in anemic patients.…”
Section: Discussionmentioning
confidence: 95%
“…Time to death due to end-stage renal disease in individuals living with HIV is significantly shorter for those with low hemoglobin values compared to normal values [26]. Kidney-related morbidities, such as albuminuria and renal hyperfiltration, are also highly correlated with HIV infection and low hemoglobin [27].…”
Section: Discussionmentioning
confidence: 99%
“…Our studies have demonstrated that patients with proteinuria have an increased prevalence of anaemia, independent to renal function [36]. However, neither the urinary excretion of erythropoietin nor its fractional excretion appears to be significantly increased in diabetes in the absence of heavy protein losses [69].…”
Section: The Renal Erythropoietin Response In Diabetesmentioning
confidence: 97%